2017
DOI: 10.1371/journal.pone.0174669
|View full text |Cite
|
Sign up to set email alerts
|

Comparative gene expression analysis of Porphyromonas gingivalis ATCC 33277 in planktonic and biofilms states

Abstract: Background and objectivePorphyromonas gingivalis is a keystone pathogen in the onset and progression of periodontitis. Its pathogenicity has been related to its presence and survival within the subgingival biofilm. The aim of the present study was to compare the genome-wide transcription activities of P. gingivalis in biofilm and in planktonic growth, using microarray technology.Material and methodsP. gingivalis ATCC 33277 was incubated in multi-well culture plates at 37°C for 96 hours under anaerobic conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 67 publications
6
28
0
Order By: Relevance
“…To gain insights into the mechanisms behind the biofilm formation in H. pylori , we used RNA sequencing and carried out a comparative transcriptomic analysis between biofilm cells and those in the planktonic state. Using this approach, we observed that 8.18% of genes were significantly differentially expressed between biofilm and planktonic cells, similar to what has been reported in other bacterial systems ( 43 , 45 , 46 ). In our experimental design, we compared a static biofilm mode of growth, where attached cells adhered to the bottom of the wells, with planktonic nonattached cells in the same wells.…”
Section: Discussionsupporting
confidence: 86%
“…To gain insights into the mechanisms behind the biofilm formation in H. pylori , we used RNA sequencing and carried out a comparative transcriptomic analysis between biofilm cells and those in the planktonic state. Using this approach, we observed that 8.18% of genes were significantly differentially expressed between biofilm and planktonic cells, similar to what has been reported in other bacterial systems ( 43 , 45 , 46 ). In our experimental design, we compared a static biofilm mode of growth, where attached cells adhered to the bottom of the wells, with planktonic nonattached cells in the same wells.…”
Section: Discussionsupporting
confidence: 86%
“…To gain insights into the mechanisms behind the biofilm formation in H. pylori, we used RNA sequencing and carried out a comparative transcriptomic analysis between biofilm cells and those in the planktonic state. Using this approach, we observed that 8.18% of genes were significantly differentially expressed between biofilm and planktonic cells, similar to that reported in other bacterial systems (43,45,46). In our experimental design, we compared a static biofilm mode of growth, where attached cells adhered to the bottom of the wells, with planktonic non-attached cells in the same wells.…”
Section: Discussionsupporting
confidence: 86%
“…This observation suggests that Synechocystis growth regulation differs when cultured on an agar surface or in liquid. Data from the literature show that heterotrophic bacteria exhibit different gene expression patterns in biofilm and in planktonic growth (Imanaka et al, 2010;He and Ahn, 2011;Romero-Lastra et al, 2017). Among the genes that are up-regulated under biofilm conditions, some encode proteins located in the outer membrane or cell envelope and involved in transport or binding (Romero-Lastra et al, 2017).…”
Section: Is Stationary Phase Reached Because Of Metabolic/ Nutrient Lmentioning
confidence: 99%
“…Data from the literature show that heterotrophic bacteria exhibit different gene expression patterns in biofilm and in planktonic growth (Imanaka et al, 2010;He and Ahn, 2011;Romero-Lastra et al, 2017). Among the genes that are up-regulated under biofilm conditions, some encode proteins located in the outer membrane or cell envelope and involved in transport or binding (Romero-Lastra et al, 2017). Furthermore, a significant number of the genes differentially expressed encode for proteins of unknown functions (Imanaka et al, 2010).…”
Section: Is Stationary Phase Reached Because Of Metabolic/ Nutrient Lmentioning
confidence: 99%